1982
DOI: 10.1104/pp.69.6.1382
|View full text |Cite
|
Sign up to set email alerts
|

Transport of the Herbicide 3-Amino-1,2,4-Triazole by Cultured Tobacco Cells and Leaf Protoplasts

Abstract: Transport of the herbicide amitrole (3-amiao-1,2,4-triazole) by suspension cultured cells and leaf protoplasts of Nicotiana tahacum cv. Wisconsin 38 has been investigated. Cells were batch-cultured and routinely assayed 3 days after subculturing. Uptake rate was pH-independent, energy independent, and culture growth phase-dependent, with growing cells exhibiting the highest rates. At a concentration of 0.2 miimolar amitrole, uptake rates yielded a Qlio of 1.6 in the 18 to 28°C temperature range. Amitrole was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…In this regard, the passive absorption of amitrole is similar to that seen for many xenobiotic compounds in plants, including, for example, monuron (5), glyphosate (9), and oxamyl (12). A report that documents the mechanism of uptake of amitrole by suspension-cultured tobacco cells and protoplasts reaches similar conclusions as to the passive noncarrier-mediated uptake of this molecule (16).…”
Section: Discussionsupporting
confidence: 57%
“…In this regard, the passive absorption of amitrole is similar to that seen for many xenobiotic compounds in plants, including, for example, monuron (5), glyphosate (9), and oxamyl (12). A report that documents the mechanism of uptake of amitrole by suspension-cultured tobacco cells and protoplasts reaches similar conclusions as to the passive noncarrier-mediated uptake of this molecule (16).…”
Section: Discussionsupporting
confidence: 57%
“…The by Pi. On the other hand, nonsaturable absorption of the d to new bentazon-free herbicides amitrole and atrazine indicated these herbicides e Fisher's LSD value for moved across cell membranes by diffusion (14,18). The significance.…”
Section: Metabolic Inhibitorsmentioning
confidence: 99%
“…From these studies, most herbicides have been shown to be transported passively across the lipid bilayer into protoplasts, with diffusion as the likely driving force. Amitrole uptake into tobacco protoplasts was reported to be via an energy-independent, noncamer-mediated process (Singer and McDaniel, 1982). Studies of protoplasts from maize roots showed that triazines moved rapidly into protoplasts with maximal accumulation occurring after 10 s of incubation (Darmstadt et al, 1983(Darmstadt et al, , 1984.…”
mentioning
confidence: 99%